2019
DOI: 10.1097/scs.0000000000005848
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Fossa and New Angle Measurements: Lateral Lamella-Cribriform Plate Angle

Abstract: Objectives: The authors investigated the olfactory fossa (OF) in patients with unilateral nasal septal deviation (NSD) and presented the lateral lamella-cribriform plate angle (LLCPA). Methods: Paranasal sinus computed tomography images of 300 adult subjects with unilateral NSD (111 males, 189 females) were evaluated retrospectively. Septal deviation angle (SDA), Keros Classification, OF depth and width, LLCPA; and orbital plate and cribriform plate (OP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 19 publications
3
11
0
Order By: Relevance
“…In our study, the most common were Keros type II (71.9%), followed by Keros type I (17.8%), Keros type III (10.3%). While a few studies reported the most common Keros type I [1,2,7,20,21], most studies were the most common type II [3][4][5]8,[13][14][15][17][18][19][22][23][24][25][26][27][28], consistent with our study. The distributions according to the Keros classification in the studies conducted in the Turkish population are presented in Table 6.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, the most common were Keros type II (71.9%), followed by Keros type I (17.8%), Keros type III (10.3%). While a few studies reported the most common Keros type I [1,2,7,20,21], most studies were the most common type II [3][4][5]8,[13][14][15][17][18][19][22][23][24][25][26][27][28], consistent with our study. The distributions according to the Keros classification in the studies conducted in the Turkish population are presented in Table 6.…”
Section: Discussionsupporting
confidence: 90%
“…Asal et al reported that the relationship of lower lateral lamella cribriform plate angles with Keros III would be more dangerous during ESS because of increased risk of trauma to the lateral lamella and intracranial penetration. 26 No formal analysis was performed but our data suggests a similar observation, there is hypothesis that lesser the angle of the lateral lamella, more of the skull base covered by thin bone. 27 This is important to consider in patients with low Keros scores.…”
Section: Discussionsupporting
confidence: 69%
“…Asal et al reported that the relationship of lower lateral lamella cribriform plate angles with Keros III would be more dangerous during ESS because of increased risk of trauma to the lateral lamella and intracranial penetration. 26 We believe this is not clinically significant when considering iatrogenic injury to the cribriform, as the depth and narrowness of the OF will not change greatly within that range. Asal et al reported that the relationship of lower lateral lamella cribriform plate angles with Keros III would be more dangerous during ESS because of increased risk of trauma to the lateral lamella and intracranial penetration.…”
Section: Discussionmentioning
confidence: 96%
“…This was in accordance with a past study, who also concluded that type olfactory fossa was the most frequently found in 70% of the 450 skull specimens they studied. 17 The frequency of type-I and type-II was 12% and 18%, respectively. The findings of Elwany et al also corresponded with our results which found that type-II olfactory fossa was most frequently found in the Egyptian population being present in 56.8% of the cases while type-I was present in 42.5% of the cases.…”
Section: Discussionmentioning
confidence: 95%